Circulating MicroRNAs As Potential Biomarkers for Veterinary Infectious Diseases - Dong, Hao; Gao, Qiang; Peng, Xiaowei; Sun, Yu; Han, Tao; Zhao, Bolin; Liu, Yufu; Wang, Chuanbin; Song, Xiaohui; Wu, Jiajun; Yang, Lin (Frontiers in Veterinary Science, 2017)
MicroRNAs (miRNAs) are a class of small non-coding RNA molecules that regulate a wide range of biological processes at post-transcriptional level. At present, over 2000 miRNAs have been discovered in humans. Many of them are found to be linked to various kinds of diseases and are being pursued as clinical diagnostics and as therapeutic targets. With the recent discovery of remarkably stable circulating miRNAs in various kinds of mammalian body fluids, the potential of circulating miRNAs as diagnostic/prognostic biomarkers of infectious diseases aroused great interest among the researchers. Unlike studies in human diseases, where some miRNA-based molecules have progressed to clinical application, in veterinary medicine, this concept is just starting to come into view. In this review, we present an update of preclinical studies on using circulating miRNAs as diagnostic biomarkers to combat infectious disease that affect domestic animals .